Risk factors for the development of a second melanoma in patients with cutaneous melanoma. (20th May 2020) - Pastor‐Tomás, N.; Martínez‐Franco, A.; Bañuls, J.; Peñalver, J.C.; Traves, V.; García‐Casado, Z.; Requena, C.; Kumar, R.; Nagore, E.
Abstract: Background: Cutaneous melanoma patients have an increased risk of developing other neoplasms, especially cutaneous neoplasms and other melanomas. Identifying factors associated with an increased risk might be useful in the development of melanoma guidelines. Objectives: To identify risk factors related to the development of a second primary melanoma in a series of patients diagnosed with sporadic melanoma and to establish the estimated incidence rate. Methods: A longitudinal study based on prospective follow‐up information of patients diagnosed with sporadic cutaneous melanoma at our centre from 2000 to 2015 was performed. Cumulative incidence was estimated based on competing risk models, and the association of characteristics with the risk of a second melanoma was performed by Cox proportional hazard models. Results: Out of 1447 patients included in the study, after a median follow‐up of 61 months, 55 patients (3.8%) developed a second melanoma. Fair hair colour, more than 100 common melanocytic nevi and the presence of more than 50 cherry angiomas were independently associated with the development of a second melanoma. The site and the histological subtype of the first and second melanomas were not consistent. The second melanomas were thinner than the first ones. Conclusions: Fair‐haired and multiple‐nevi patients might benefit from more intensive prevention measures. The finding of cherry angiomas as a risk factor suggests that these lesions could be markers of skin sun damage in the setting of certain degree of genetic susceptibility. Abstract : Linked articles : A. Villani et al. J Eur Acad Dermatol Venereol 2020; 34 : e623–e624. https://doi.org/10.1111/jdv.16500